1979
DOI: 10.1071/bt9790631
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Australian and Some Overseas Populations of Emex australis and E. spinosa

Abstract: Australian populations of the widespread Emex australis and the more restricted E. spinosa were tested for subspecific variation. The plants were grown for two generations in a glasshouse from seed collected from field populations. The results from growing the first generation showed that two groupings of E. australis could be made on the basis of hierarchical grouping analysis, but the populations were much more similar in the second generation and such groupings could not be made. There were no marked differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Martins and Jain (1978) found a similar spread of colonizing effort in their experimental introductions of Trifolium hirtum. There was evidence that late-emerging T. hirtum plants were genetically distinct (Martins & Jain 1978), but such is not likely to be the case for Australian Emex populations (Weiss & Simmons 1979;Panetta 1990). The presence of seed dormancy may incur costs during colonizing episodes (Venable & Brown 1988) but such costs are reduced when the probability of seed survival is high (Brown & Venable 1986).…”
Section: Discussionmentioning
confidence: 93%
“…Martins and Jain (1978) found a similar spread of colonizing effort in their experimental introductions of Trifolium hirtum. There was evidence that late-emerging T. hirtum plants were genetically distinct (Martins & Jain 1978), but such is not likely to be the case for Australian Emex populations (Weiss & Simmons 1979;Panetta 1990). The presence of seed dormancy may incur costs during colonizing episodes (Venable & Brown 1988) but such costs are reduced when the probability of seed survival is high (Brown & Venable 1986).…”
Section: Discussionmentioning
confidence: 93%
“…The validity of a correlative model such as BiocLiM is dependent on the genetic homogeneity of the investigated species (Howden, 1985), at least with regard to climatic response. South African and Australian populations of Emex exhibit very little variation in growth, reproductive and isozyme characteristics (Weiss & Simmons, 1979;Panetta, 1990c), Chondrilla comprises three apomictic forms in Australia, but any differences in their respective Australian distributions have been due to historical factors (Panetta & Dodd, 1987b), Nothing is known about the levels of genetic variation in Australian populations of Homeria, but this is a species whose Australian distribution is chmatically similar to its region of origin Prediction of weediness 281 (Michael, 1981), In general, the reliability of predictions should be lower when a species possesses a wide climatic tolerance, whether this arises through high levels of genetic variation or through plasticity.…”
Section: Reliability Of Predictions Based On Homoclime Analysismentioning
confidence: 99%
“…On the other hand, the fact that the other three populations in Victoria, Queensland and the Eyre Peninsula of South Australia are genetically distinct, both from the original Western Australian introduction and each other, strongly suggests that they represent independent introductions into Australia from overseas. This suggestion is supported by the studies of Weiss and Simmons (1979) who found that individuals from the Queensland population differed in a number of morphological attributes from those from the Victorian and Eyre Peninsula populations. The alternative explanation that the original introduction into Western Australia was highly polymorphic, gave rise to subcolonies in three other States and then, in recent years, lost its variability, seems less plausible.…”
Section: Ffmentioning
confidence: 63%
“…The first recorded sightings in South Australia were at Port Pirie in 1973 and the Eyre Peninsula in 1974 and in Victoria at Merbein in 1974 (Gilbey 1974;Weiss and Julien 1975). Whether the populations in Queensland, South Australia and Victoria came from Western Australia or represent separate introductions from overseas is currently unknown (Weiss and Simmons 1979).…”
Section: Introductionmentioning
confidence: 99%